The Green Marketing Mix as a Determinant of Green Purchase Decisions for Sustainability Based SME Products in Kerinci Regency - Anggil Nopra Lova; Indra Budaya; Melifia Liantifa (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
ABSTRACT The study purpose was the effect of the green marketing mix comprising green product, green price, green placement, and green promotion on green purchase decisions for sustainability-based SME products in Kerinci Regency. Materials and methods. An explanatory quantitative approach was employed, with data collected through structured questionnaires from 190 purposively selected respondents. Multiple linear regression was applied for data analysis. Results. The results indicate that all dimensions of the green marketing mix have positive and significant effects on green purchase decisions, both partially and simultaneously. The coefficient of determination (R²) of 0.855 reveals that 85.5% of the variance in green purchase decisions is explained by the four independent variables, with green promotion emerging as the most dominant factor, followed by green placement, green price, and green product. Conclusions. These findings confirm that a comprehensive and consistent implementation of the green marketing mix plays a decisive role in shaping sustainable consumer purchasing behavior, particularly within the regional SME context.